UPAYA MENINGKATKAN PARTISIPASI BELAJAR PESERTA DIDIK MENGGUNAKAN MEDIA INTERAKTIF LUMIO BY SMART DENGAN MODEL PEMBELAJARAN KOOPERATIF LEARNING - Sanam, Maria; Fontes, Isabela Sintia; Putri, Maria Indriani; Larasati, Dian Ayu; Murwanti, Dwi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Student learning participation in class 8 D of SMPN 1 Surabaya is still necessary improved because the learning process is still centered on the teacher and students just listen and pay attention so that the level of participation and activity students also need to be improved. . This research aims to increase students' learning participation using Lumio By Smart interactive media in class 8 social studies at Smpn 1 Surabaya. This research uses the classroom action method with two action cycles, each cycle consisting of four stages, namely planning, action implementation, observation and evaluation, and analysis and reflection. The sample for this research was 33 Class 8 D students with 17 female students and 16 male students. Data Collection Through Questionnaires, Observations and Interviews. Data were analyzed descriptively and qualitatively. Scores and questionnaires were calculated using a Likert scale. A significant increase in student learning participation can be seen in students who are active in learning after using the interactive learning media Lumio by Smart. In cycle one, 59.63 percent of students participated in learning, while in cycle 2 there was an increase to 85.56 percent. Keywords: Lumio by smart,participation learning